171k views
0 votes
5/3x - 2y=-2
-x+y=2




1 Answer

3 votes

Answer:

(6/11, 16/11)

Explanation:

While it's fairly obvious that you're supposed to "solve this system of equations," it'd be clearer if you were to say so specifically. Also, reduce ambiguity by using parenthes: You meant either (5/3)x or 5/(3x). Which one? I'm assuming it's (5/3)x.

Then our system is:

(5/3)x - 2y = -2

x + y = 2

Let's eliminate y through addition/subtraction. Multiply the 2nd equation through by +2:

(5/3)x - 2y = -2

2x + 2y = 4

------------------------

(11/3)x = 2

Multiplying both sides by 3 eliminates the fractional coefficient:

11x = 6

Then x = 6/11. Now we must solve for y:

-(6/11) + y = 2

Multiplying 2 by 11/11 yields:

-(6/11) + y = 22/11.

This simplifies to y = 16/11

Thus, the solution of this system is

(6/11, 16/11)

User Martin Sherburn
by
5.3k points